Energy and mobility conscious multipath routing protocol for route stability and load balancing in MANET‐IoT networks - Jabbar, Waheb A.; Mahamod, Ismail; Roshahliza, M. Ramli (2018)
Internet of Things is the key technology and enabler of Industrial Revolution IR 4.0. The recent advances of smart devices with embedded sensors will enable global connectivity of MANET-IoT scenarios with heterogeneous devices in terms of energy resources and mobility. Routing protocols play crucial roles in providing effective and efficient communication for data transmission to successfully implement the IoT networks.